2020
DOI: 10.20944/preprints202009.0498.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy Engineering Approach for Rural Areas Cattle Farmers in Bangladesh to Reduce COVID-19 Impact on Food-Safety

Abstract: This paper reports on the optimization of thin-film coating assisted self-sustainable off-grid hybrid power generation systems for cattle farming in rural areas of Bangladesh. Bangladesh is a lower middle-income country with declining rates of poverty among its 160 million people due to persistent economic growth in conjunction with balanced agricultural improvements. Most of the rural households adopt a mixed farming system by cultivating crops and simultaneously rearing livestock. Among the animals raised, c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similarly, Gregorioa and Ancog (2020) concluded that, in Southeast Asia, the experience of this pandemic should be drawn upon to ensure food safety by treating it as a coordinated problem between the public and private sectors. In a study carried out in Bangladesh, Nur-E-Alam et al (2020) recommended meeting citizens’ food needs with local supplies to minimise the risk of impacts on food safety. By drawing on Internet survey data of 1,373 residents in China, Min et al (2020) found that consumers’ food safety knowledge has a significant and positive effect on their food safety behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gregorioa and Ancog (2020) concluded that, in Southeast Asia, the experience of this pandemic should be drawn upon to ensure food safety by treating it as a coordinated problem between the public and private sectors. In a study carried out in Bangladesh, Nur-E-Alam et al (2020) recommended meeting citizens’ food needs with local supplies to minimise the risk of impacts on food safety. By drawing on Internet survey data of 1,373 residents in China, Min et al (2020) found that consumers’ food safety knowledge has a significant and positive effect on their food safety behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…So far we have conducted a slightly different research work (simulation based) based on this concept and reported in a high impact journal "Sustainability" [45]. In the reported article, we demonstrated the design and optimization of a thin-film coating-assisted, self-sustainable, energy-efficient and cost-effective off-grid hybrid (photovoltaic-battery-generator) power system suitable for advanced cattle farming in Bangladesh which is a new and forward-looking approach for sustainable development of the livestock sector.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported article, we demonstrated the design and optimization of a thin-film coating-assisted, self-sustainable, energy-efficient and cost-effective off-grid hybrid (photovoltaic-battery-generator) power system suitable for advanced cattle farming in Bangladesh which is a new and forward-looking approach for sustainable development of the livestock sector. Based on the simulation results, we recommended that energy engineering together with the advanced building material coatings can be the model for modern farming in any rural areas, and can help to reduce the carbon emission footprint as well [45]. However, the practical demonstration of this work is an on-going research program within our group depending on the availability of sufficient research funds.…”
Section: Discussionmentioning
confidence: 99%